Water Quality Model in Jambi Province using Geographically Weighted Regression - Yuinanda, Sherli; Multahadah, Cut; Marisa, Hasnaul; Abdullah, Mohammad (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
PDAM (Regional Water Supply Company) functions to serve the needs of many people's lives by providing quality water for the community. Based on Permenkes no. 492/menkes/per/iv/2010 clean water quality parameters, namely the feasibility of water used in daily life related to physical, chemical and microbiological parameters including Biological Oxygen Demand (BOD), Total Dissolved Solid (TDS), Cloride (Cl), and Nitrates (NO3). The aim of this research is to test the water quality of PDAMs in Jambi Province based on minimum quality standards for clean water Using Geographically Weighted Regression (GWR) with the assumption. The method can be used to model the relationship between the dependent variable and the independent variable has regional influence. The results showed that the BOD values of all regions in Jambi province met except for Merangin, which was 2.1 mg/l with a threshold value of 2.0 mg/l. For other parameters, namely TDS, Cl and NO3, they meet the threshold values. Based on the results of the GWR model, the coefficient ofÂ  is 0.669 , this means that there is a relationship between TDS, Cl and NO3 to BOD and is positive.